Dental arch dimensional changes after adenoidectomy or tonsillectomy in children with airway obstruction: A meta-analysis and systematic review under PRISMA guidelines. Issue 39 (September 2016) - Zhu, Yanfei; Li, Jiaying; Tang, Yanmei; Wang, Xiaoling; Xue, Xiaochen; Sun, Huijun; Nie, Ping; Qu, Xinhua; Zhu, Min
Abstract: Background: Children with severe airway obstruction tend to have a vertical direction of growth, class II malocclusion, and narrow arches. Adenoidectomy and tonsillectomy were recommended for the promotion of balanced dentition growth in these children. The aim of this study was to determine the effect of adenoidectomy and tonsillectomy on the growth of dental morphology in children with airway obstruction. Methods: A comprehensive search of the Medline, Embase, Web of science, and OVID databases for studies published through to January 17, 2016 was conducted. Prospective, comparative, clinical studies assessing the efficacy of adenoidectomy, or tonsillectomy in children with airway obstruction were included. The weighted mean difference (WMD) and 95% confidence interval (CI) were used for continuous variables. Forest plots were drawn to demonstrate effects in the meta-analyses. Results: Eight papers were included in our study. We found that adenoidectomy and tonsillectomy led to a significant change in nasal-breathing in children with airway obstruction. Children with airway obstruction had a significantly narrower posterior maxillary dental arch than children without airway obstruction (WMD = −0.94, 95% CI [−1.13, −0.76]; P  < 0.001). After surgery, these children still had a significantly narrower dental arch than the nasal-breathing children (WMD = −0.60, 95% CI [−0.79, −0.42]; P  < 0.001). In terms of dental arch width, malocclusion, palatal height, overjet, overbite, dental arch perimeter, and arch length, a tendency toward normalization was evident following adenoidectomy or tonsillectomy, with no significant differences evident between the surgical group and the normal group. The small number of studies and lack of randomized controlled trials were the main limitations of this meta-analysis. Conclusions: Following adenoidectomy and tonsillectomy, the malocclusion and narrow arch width of children with airway obstruction could not be completely reversed. Therefore, other treatments such as functional training or orthodontic maxillary widening should be considered after removing the obstruction in the airway. Abstract : Supplemental Digital Content is available in the text